Retained abdominal gallstones during laparoscopic cholecystectomy - TÜNEY, DAVUT; GÜLLÜOĞLU, MAHMUT BAHADIR; YEGEN, ŞEVKET CUMHUR (EXCERPTA MEDICA INC-ELSEVIER SCIENCE INC, 2005)
Background: Although gallbladder perforation with spillage of bile and gallstones is quite common, the approach to retained gallstones in the abdomen still is controversial. Methods: Laparoscopic cholecystectomy (LC) was performed on 580 patients with gallstones. In 101 (17%) patients, gallbladder perforations occurred during surgery, and in 43 (7%) patients, stone(s) were spilled into the peritoneal cavity. In 24 (4%) patients, gallstone(s) were not cleared entirely from the peritoneal cavity. These patients were invited to return for physical examination and biochemical tests. To investigate the retained abdominal gallstone(s) computed tomography was performed. Results: Twenty-two patients were investigated. After a median follow-up period of 121 months, retained abdominal gallstone(s) were shown in 2 patients by computed tomography. Biochemical tests were normal except in 1 patient with chronic hepatitis. All of the patients were happy with their surgical results. Conclusions: This study revealed no harm caused by retained abdominal gallstone(s) during LC after long-term follow-up evaluation. (c) 2005 Excerpta Medica Inc. All rights reserved.
Keywords: laparoscopy; cholecystectomy; retained abdominal gallstone; UNRETRIEVED GALLSTONES; SPILLED GALLSTONES; PERITONEAL-CAVITY; STONES; LOST